2007
DOI: 10.1258/135763307783247392
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of a system for neonatal teleconsultation

Abstract: We assessed the efficacy of a system for teleconsultation in the care of newborns via real-time video (NEMO, Neonatal Examination and Management Online). The study was conducted in the controlled environment of a tertiary neonatal intensive care unit (NICU) before deployment for trial in remote hospitals. Eight ventilated infants were studied (their parents providing consent). A range of clinical tasks were completed by 14 medical staff. These included visual assessment of respiratory rate and perfusion, gathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Telemedicine was conducted using the NEMO (Neonatal Examination and Management Online) system. 2,3 Systems were installed at the tertiary neonatal intensive care unit (NICU) at the Royal Brisbane and Women's Hospital (RBWH) and nurseries at four peripheral hospitals in Queensland (Caboolture, Redcliffe, Nambour and Hervey Bay Hospitals).…”
Section: Introductionmentioning
confidence: 99%
“…Telemedicine was conducted using the NEMO (Neonatal Examination and Management Online) system. 2,3 Systems were installed at the tertiary neonatal intensive care unit (NICU) at the Royal Brisbane and Women's Hospital (RBWH) and nurseries at four peripheral hospitals in Queensland (Caboolture, Redcliffe, Nambour and Hervey Bay Hospitals).…”
Section: Introductionmentioning
confidence: 99%
“…The consultations range from management of common neonatal problems in a center without neonatal specialists to management of critically ill neonates with complex needs in collaboration with local neonatal expertize. These services are valuable in obtaining expert consultations, avoiding transfers for patients who can be 1 The University of Texas Southwestern Medical Center, USA 2 Children's Medical Center of The Children's Health System of Texas, USA 3 Parkland Health and Hospital System, USA managed safely at the local facilities, and aiding in management of critically ill infants prior to transportation. Armfield et al reported one of the earliest examples of the successful use of telemedicine for acute neonatology consultations between a tertiary NICU and newborn nurseries.…”
Section: Introductionmentioning
confidence: 99%
“…Armfield et al reported one of the earliest examples of the successful use of telemedicine for acute neonatology consultations between a tertiary NICU and newborn nurseries. 2,3 Also, teleneonatology programs have shown promising results in newborn resuscitation assistance, 4,5 education dissemination and infant mortality reduction through improved perinatal regionalization. [6][7][8] In 2013, Children's Health System of Texas and University of Texas Southwestern Medical Center collaborated to establish TeleNICU at the Children's Medical Center (CMC) Dallas, the first neonatal telemedicine program in the State of Texas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the lack of publications demonstrating its clinical benefits or cost-effectiveness in neonatology, telemedicine is being used in the neonatal population and there does appear to be a positive perception for remote consultations. 9 The aim of our present study was to assess the feasibility and acceptability of a patient-rounding model (''tele-rounding'') utilizing remote-controlled, real-time telemedicine technology compared to the conventional on-site care model. We sought to describe a method to utilize and integrate telemedicine in the daily clinical practice of a neonatologist.…”
Section: Introductionmentioning
confidence: 99%